Sufism-Based Entrepreneurship as a Model for Strengthening the Economic Independence of Pesantren Students - M. Anis Bachtiar; Rozaqul Arif; Muhammad Haidarsyah Kasyfillah; Hizhwah Aqidatul Izzah (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This study aims to explain the relationship between Islamic asceticism, the internalization of spiritual values, psychological motivation, and the entrepreneurial behavior of students at Roudhotul Muttaqin Islamic Boarding School, Mojokerto. A qualitative case study approach was employed, utilizing in-depth interviews, observations, documentation, and focus group discussions (FGDs) involving eight informants. The findings reveal that the practice of Islamic asceticism through dhikr, wirid, voluntary prayers, and the internalization of values such as sincerity (ikhlas), patience (sabr), trust in God (tawakkul), steadfastness (istiqamah), asceticism (zuhud), and gratitude (shukr) fosters a spiritually grounded work ethic among students engaged in aquaculture activities. Entrepreneurial activities are understood not merely as economic endeavors but also as a form of da'wah bil hal (preaching through action) and tazkiyat al-nafs (spiritual purification), cultivating discipline, mental resilience, honesty, and social responsibility. Business setbacks are interpreted as opportunities for muhasabah (self-reflection) and spiritual learning, strengthening the character of resilient entrepreneurs. This study proposes a Sufism-based entrepreneurship model grounded in the psychology of da'wah, linking Islamic asceticism, spiritual motivation, and entrepreneurial behavior while reinforcing the paradigm of transformative da'wah through productive spirituality.